General Social Survey, 1972-2016 (Cumulative File) - Smith, Tom W. ([Verlag nicht ermittelbar], 2017)
Since 1972, the General Social Survey (GSS) has been monitoring societal change and studying the growing complexity of American society. The GSS aims to gather data on contemporary American society in order to monitor and explain trends and constants in attitudes, behaviors, and attributes; to examine the structure and functioning of society in general as well as the role played by relevant subgroups; to compare the United States to other societies in order to place American society in comparative perspective and develop cross-national models of human society; and to make high-quality data easily accessible to scholars, students, policy makers, and others, with minimal cost and waiting. GSS questions include such items as national spending priorities, marijuana use, crime and punishment, race relations, quality of life, and confidence in institutions. Since 1988, the GSS has also collected data on sexual behavior including number of sex partners, frequency of intercourse, extramarital relationships, and sex with prostitutes. In 1985 the GSS co-founded the International Social Survey Program (ISSP). The ISSP has conducted an annual cross-national survey each year since then and has involved 58 countries and interviewed over one million respondents. The ISSP asks an identical battery of questions in all countries; the U.S. version of these questions is incorporated into the GSS. The 2016 GSS added in new variables covering information regarding social media use, suicide, hope and optimism, arts and culture, racial/ethnic identity, flexibility of work, spouses work and occupation, home cohabitation, and health.